Retinal Capillary Rarefaction in Patients with Type 2 Diabetes Mellitus - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Friedrich, Stefanie; Kistner, Iris; Striepe, Kristina; Schmieder, Roland (PLoS ONE, 2016)
In diabetes mellitus type 2, capillary rarefaction plays a pivotal role in the pathogenesis of end-organ damage. We investigated retinal capillary density in patients with early disease.This cross-sectional study compares retinal capillary rarefaction determined by intercapillary distance (ICD) and capillary area (CapA), measured non-invasively and in vivo by scanning laser Doppler flowmetry, in 73 patients with type 2 diabetes, 55 healthy controls and 134 individuals with hypertension stage 1 or 2.In diabetic patients, ICD was greater (23.2±5.5 vs 20.2±4.2, p = 0.013) and CapA smaller (1592±595 vs 1821±652, p = 0.019) than in healthy controls after adjustment for differences in cardiovascular risk factors between the groups. Compared to hypertensive patients, diabetic individuals showed no difference in ICD (23.1±5.8, p = 0.781) and CapA (1556±649, p = 0.768).In the early stage of diabetes type 2, patients showed capillary rarefaction compared to healthy individuals.
EVALuna2:3920